Mechanisms that accelerate the diffusion of renewable technologies in new markets: Insights from the wind industry in Portugal - Bento, N. (2014)
The spatial diffusion of sustainable innovations and the importance of local absorptive capacity in early adoption are studied through the comparison of the diffusion of wind energy in Denmark and Portugal. The novelty of this research consists in revealing patterns of spatial growth and explaining them with the help of concepts issued from the sustainability transitions literature. In particular, the technological innovation systems approach and the actor-oriented analysis focusing on the role of organizations and networks in the emerging innovation systems. An acceleration of diffusion was found in the case of wind technologies in Portugal in comparison with the “core”. The analysis permitted to identify some key drivers of this process. In a first exploratory stage, science and technology policies emerged as initial “motor” of change supporting the fulfillment of critical functions of the innovation system (e.g. knowledge development, experimentation). In the implementation stage, the market took off induced by an attractive feed-in-tariff that enabled the formation of expectations. This attracted key actors whose advocacy coalitions have gradually got the capacity to influence policy making, which contributed to further speed up market formation. Diffusion acceleration was possible thanks to a series of partnerships with international manufacturers for the transfer of state-of-the-art technology from “core” countries, and to the enhancement of absorptive capacity that permitted to better assimilate transferred knowledge and integrate it with local competences.